Alcohol-Paired Contextual Cues Produce an Immediate and Selective Loss of Goal-directed Action in Rats - Ostlund, Sean B.; Maidment, Nigel T.; Balleine, Bernard W. (Frontiers in Integrative Neuroscience, 2010)
We assessed whether the presence of contextual cues paired with alcohol would disrupt rats’ capacity to express appropriate goal-directed action control. Rats were first given differential context conditioning such that one set of contextual cues was paired with the injection of ethanol and a second, distinctive set of cues was paired with the injection of saline. All rats were then trained in a third, neutral context to press one lever for grain pellets and another lever for sucrose pellets. They were then given two extinction tests to evaluate their ability to choose between the two actions in response to the devaluation of one of the two food outcomes with one test conducted in the alcohol-paired context and the other conducted in the control (saline-paired) context. In the control context, rats exhibited goal-directed action control; i.e., they were able selectively to withhold the action that previously earned the now devalued outcome. However, these same rats were impaired when tested in the alcohol-paired context, performing both actions at the same rate regardless of the current value of their respective outcomes. Subsequent testing revealed that the rats were capable of overcoming this impairment if they were giving response-contingent feedback about the current value of the food outcomes. These results provide a clear demonstration of the disruptive influence that alcohol-paired cues can exert on decision-making in general and goal-directed action selection and choice in particular.